Gender differences in suicide in Serbia within the period 2006–2010 - Dedić, Gordana (Vojnosanitetski pregled, 2014)
Background/Aim. The complex multifactorial etiology of suicide suggests the need to consider gender differences when developing effective strategies for suicide prevention. The aim of this study was to examine the suicide rates and/or trends obtained for population as a whole, including gender differences in cases of committed suicide and to consider factors (age groups, education, employment, marital status, nationality and methods) associated with it in Serbia within the period 2006–2010. Methods. Data were obtained from the Statistical Office of the Republic of Serbia. Their classification related to the suicide method was carried out on the basis of ICD-X Code, WHO 1992 (International Statistical Classification of Diseases and Related Health Problems 10th revision, World Health Organization). Statistical analysis was done by using the crude specific suicide rate. Results. Within the period 2006–2010 the total number of suicides in Serbia was 6,673, of which 71.9% were males and 28.1% females (male to female suicide ratio 2.56 : 1). Their average rate was 18.15 per 100,000 persons, namely, 26.85 per 100,000 for males and 9.92 per 100,000 for females. Suicide was most often committed by married males and females with high school education, retired, by the Serbs. The suicide rate in Serbia increased paralelly with the age of suicide committers and it was the highest in subjects of both genders aged over 75 years. The most common suicide method in males (62.78%) and in females (58.38%) was hanging and strangling. The second most common method in males was by firearm (18.65%) and in females poisoning (19.26%). Conclusions. Suicide prevention Programme should be primarily oriented toward the male population because it is more exposed to stress in the period of social transition, but males are still less ready to ask for doctor's help when having some problems with mental health.
Keywords: suicide; serbia; gender identity; risk factors